EFFECT OF CHANGE MANAGEMENT ON EMPLOYEE ATTITUDE IN LAFARGE CEMENT PLC CROSS RIVER STATE, NIGERIA - Margaret, Agbor (The journal of contemporary issues in business and government, 2024)
This study carried out a review of the effect of change management on employee attitude in Lafarge Cement Plc Cross River State, Nigeria. The study used examined Lewin’s theory of behaviour to provide a theoretical foundation for the study. Primary data was used for the study and they were obtained using structured questionnaire from a sample of 109 senior staff of Lafarge Cement Plc Cross River State. Multiple regression analysis was used for the study and the hypotheses of the study were tested using the probability value of the regression estimates. The findings of the study indicates that innovation management has a positive effect on employee attitude in Lafarge Cement Plc Cross River State, Nigeria and the effect is statistically significant (p<0.005). Resource management has a positive effect on employee attitude in Lafarge Cement Plc Cross River State, Nigeria and the effect is statistically significant (p<0.005). Training was found to have a negative effect on employee attitude in Lafarge Cement Plc Cross River State, Nigeria and the effect is not statistically significant (p>0.005). It was concluded that for change to succeed, the human aspect to change management must be successfully addressed in order to avoid resistance to change. It was recommended among others that the management of the Lafarge Cement Plc Cross River State Nigeria can bring about effective change management in the industry if they utilize the potent power of training, which can be on-the-job or off-the-job training. This is because, training and development of employees equips them with the requisite skills to handle both planned and unplanned change in the industry and give the company competitive advantage.